Kebijakan Perlindungan Pekerja Migran Perempuan Kabupaten Blitar - Ikmal, Novita Maulida; Holifah, Nur; Indriastuti, Indriastuti; Prabowo, Veny (SPECTRUM: Journal of Gender and Children Studies, 2025)
This study aims to analyze the strategies and challenges in implementing gender-responsive protection policies for Indonesian migrant workers. Migrant worker protection is a strategic issue that requires attention to gender equality, given that the majority of migrant workers are women and are vulnerable to discrimination, violence, and exploitation. This study uses a qualitative descriptive approach, collecting data through in-depth interviews, observations, and reviewing policy documents at the central and regional levels, particularly at the One-Stop Integrated Service (LTSA). The results indicate that the main strategies for policy implementation include strengthening institutional capacity, providing gender-based services, improving legal literacy for migrant workers, and strengthening inter-agency cooperation. However, implementation still faces various challenges, including limited human resources with a gender perspective, suboptimal cross-sectoral coordination, and minimal policy dissemination at the grassroots level. This study recommends the need to integrate a gender perspective into every stage of migrant worker protection, increase gender-responsive budgets, and involve civil society in policy oversight.